Sustainability Reporting Disclosure: The Role of Audit Committee Characteristics and Firm Size in Indonesian Mining Firms - Zavira, Fayza; Herawaty, Netty; Silvera, Dica Lady (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study examines the influence of audit committee characteristics and firm size on sustainability reporting in mining companies listed on the Indonesia Stock Exchange during 2020–2024. Differences between disclosed information and actual practices indicate that transparency has not been fully achieved. Background Problems The audit committee is expected to ensure the reliability of reporting and align disclosed information with actual conditions. Limitations in monitoring effectiveness raise concerns about how audit committee characteristics contribute to sustainability reporting quality. Novelty: This study analyzes audit committee characteristics, including size, independence, financial expertise, and meeting frequency, while emphasizing the gap between formal governance structures and their actual effectiveness. Research Methods: A quantitative approach is applied using panel data regression on 21 mining companies with 105 observations selected through purposive sampling. Finding/Results: The results show that audit committee size and meeting frequency have a positive and significant effect on sustainability reporting. Audit committee independence has a negative and significant effect. Financial expertise and firm size do not show a significant influence. Conclusion: Governance effectiveness is more influenced by active monitoring than formal structures. Strengthening the functional role of audit committees is essential to improve sustainability reporting quality.